How relative poverty influences responses to social protection programmes: Evidence from Pakistan - Kosec, Katrina; Mo, Cecilia Hyunjung (VoxDev, 2023)
Since the COVID-19 pandemic global income inequality has again started to rise—a trend exacerbated by the food and fertiliser crisis caused by Russia’s ongoing war in Ukraine (The Economist 2022). Increasingly common disasters (many climate-related) across the globe – such as Pakistan’s devastating 2022 floods (UNICEF 2023), ongoing severe drought in the Horn of Africa (UN News 2022), and the recent earthquake in Syria and Turkey (Francis et al. 2023) – also disproportionately affect already vulnerable groups (UNDRR 2023). Such events tend to further exacerbate the gulf between the rich and the poor. This trend toward greater income inequality is notable, given a growing body of research has demonstrated that citizens’ support for and trust in government is heavily influenced by real as well as perceived income inequality (Gimpelson and Treisman 2018, Healy et al. 2017).